BATAS PEMIDANAAN EKSPRESI SIMBOLIK SEBAGAI TINDAK PIDANA MAKAR: KAJIAN YURIDIS SERTA ANALISIS DALAM PERSPEKTIF SOBURAL - Yoanda Widi Pranata; Rendy Airlangga (Universitas Labuhanbatu, 2026)
The phenomenon of symbolic expression has generated legal debate concerning the boundary between freedom of expression and the criminal offense of treason (makar) in Indonesian criminal law. This study aims to analyze the threshold of criminal liability for symbolic expression and the application of the SOBURAL Approach (Social–Cultural–Structural) as a contextual framework. This study employs a normative juridical method with statutory, conceptual, and comparative approaches. The findings indicate that the former Criminal Code (Wetboek van Strafrecht) focuses on “commencement of execution” as the threshold of criminal liability, whereas the Indonesian National Criminal Code (Law No. 1 of 2023) expands this threshold to the stage of “preparatory acts”. The novelty of this study lies in the application of the SOBURAL Approach to understand the social, cultural, and structural context of symbolic expression, as well as the development of treason assessment parameters based on criminal law doctrine and the analysis of judicial reasoning patterns in treason-related court decisions. The boundary between symbolic expression as a form of freedom of expression and the offense of treason lies in whether the constituent elements of the offense are fulfilled. Therefore, the application of provisions on the criminal offense of treason must be conducted objectively, proportionally, and based on evidence to maintain a balance between freedom of expression and the protection of the state. Keywords: Freedom of Expression; Symbolic Expression; Indonesian National Criminal Code (Law No. 1 of 2023); The Criminal Offense of Treason (Makar); SOBURAL Approach